Implementation of the Healthy Living Community Movement (GERMAS) Policy in Bandung District - Wahyudin, Dedi; Pramudho, Kodrat; Mosjasari, Yuli Irnawaty (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2026)
Indonesia is currently facing a triple burden of disease, prompting the introduction of the Healthy Living Community Movement (GERMAS) as a national strategy to reduce non-communicable disease (NCD) risk factors through promotive and preventive actions. This study aims to analyze the implementation of Regent Regulation No. 87 of 2021 concerning the organization of GERMAS in Bandung Regency. This study employed a qualitative descriptive design. Data were collected through in-depth interviews, observations, document analysis, and focus group discussions. Informants, including government officials, health workers, and community representatives, were selected using purposive sampling. The data were analyzed using the Van Meter and Van Horn policy implementation framework. The findings indicate that the implementation of the policy remains suboptimal due to limited resources, weak inter-organizational coordination, and low community participation in routine health check-ups. To improve the effectiveness of GERMAS, local governments must prioritize strengthening cross-sectoral collaboration, allocating dedicated resources for health infrastructure, and enhancing targeted community awareness campaigns.